Efficient hydrogen storage alloy material and preparation method thereof
By optimizing element ratio and process flow, high-efficiency hydrogen storage alloy materials are prepared, which solves the problems of complex and high cost of preparation processes of traditional hydrogen storage alloy materials, and combines efficient hydrogen storage performance and long life, providing hydrogen energy storage with Low-cost, high-performance solutions.
Patent Information
- Application Number
- CN202411199992.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-13
AI Technical Summary
The preparation process of traditional hydrogen storage alloy materials is complex, costly and poor cycle stability, which limits its large-scale application.
Using specific ratios of nickel, cobalt, manganese, aluminum, lanthanum, cerium, praseodymium, neodymium and other elements, it is used to pass airflow grading, magnetic separation, drying, ball milling, hydraulics, high-frequency electromagnetic induction smelting, casting molding, surface treatment and annealing. Steps to prepare high-efficiency hydrogen storage alloy materials, optimize element ratios and process flow to improve hydrogen storage performance and cycle stability.
It achieves a balance between efficient hydrogen storage performance, long life and low cost, providing an efficient hydrogen storage material for the field of hydrogen energy storage.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen storage alloy materials, and specifically relates to a high-efficiency hydrogen storage alloy material and a preparation method thereof. Background Art
[0002] As the global demand for clean energy increases, hydrogen energy, as a clean, efficient and sustainable energy carrier, has attracted much attention for its storage and utilization technology. Hydrogen storage alloys have become a hot topic of current research due to their high hydrogen storage density, easy operation, safety and reliability. Hydrogen storage alloy materials have important application prospects in the field of hydrogen energy storage due to their high hydrogen storage density, good safety and cycle stability. However, traditional hydrogen storage alloys have problems such as complex preparation process, high cost and poor cycle stability, which limit their large-scale application. Summary of the invention
[0003] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a high-efficiency hydrogen storage alloy material and a preparation method thereof, which effectively solves the problems raised in the above background.
[0004] To achieve the above object, the present invention provides the following technical solution: a high-efficiency hydrogen storage alloy material, comprising the following components in percentage by mass:
[0005] Nickel: 49.9% to 51.1%;
[0006] Cobalt: 10.16% to 10.56%;
[0007] Manganese: 4.34% to 4.74%;
[0008] Aluminum: 1.5% to 1.9%;
[0009] Lanthanum: 20.5%-24.5%;
[0010] Cerium: 8.4% to 10.4%;
[0011] Praseodymium: 0.4% to 0.8%;
[0012] Neodymium: 0.4%~0.8%.
[0013] A method for preparing a high-efficiency hydrogen storage alloy material comprises the following steps:
[0014] Step S1, raw material preparation and pretreatment:
[0015] S1.1. Raw material selection: metal powders that meet quality requirements are selected, including nickel powder, cobalt powder, manganese powder, aluminum powder, lanthanum powder, cerium powder, praseodymium powder and neodymium powder;
[0016] S1.2, screening, using an airflow classifier to screen the raw material powder to remove particles larger and smaller than the set particle size;
[0017] S1.3, impurity removal, remove ferromagnetic impurities and non-metallic impurities in the powder by magnetic separation;
[0018] S1.4, drying treatment, placing the screened powder in a vacuum drying oven at a temperature of 80-120°C for 2-4 hours to remove moisture on the powder surface and adsorbed moisture;
[0019] Step S2: Mixing and pressing:
[0020] S2.1, powder mixing, using a ball mill for powder mixing, the speed is 300 ~ 500rpm, the mixing time is 2 ~ 4h, to ensure that the powder is mixed evenly, and anhydrous ethanol can be added as a dispersant during the mixing process to improve the mixing effect;
[0021] S2.2, pressing and molding, pouring the evenly mixed powder into a mold, using a hydraulic press to press, the pressure range is 100 ~ 300MPa, and the pressure holding time is 1 ~ 5min;
[0022] Step S3, smelting and alloying:
[0023] S3.1, during the smelting process, the pressed alloy block is placed in a high-frequency electromagnetic induction melting furnace for smelting, so that the alloy block reaches a melting point above the melting point in a relatively short time, and during the smelting process, the melt is evenly mixed by the stirring effect of electromagnetic induction, and the stirring speed is 50-100 rpm;
[0024] S3.2, repeated smelting, in order to ensure the uniformity of alloy composition and the compactness of structure, multiple smelting is required. After each smelting, the melt is poured out and put back into the furnace, and the above smelting process is repeated 3 to 4 times;
[0025] Step S4: molding and cooling:
[0026] S4.1, pouring molding, quickly pour the molten alloy liquid into a mold preheated to 100-200℃ to avoid cracks caused by excessive cooling of the alloy;
[0027] S4.2, cooling and solidification, the alloy liquid in the mold gradually solidifies and forms the required alloy block under natural cooling;
[0028] Step S5, post-processing:
[0029] S5.1. Surface treatment: sandblasting, grinding or chemical treatment of the formed alloy block to remove surface defects and oxide layers and improve the hydrogen absorption and desorption properties of the alloy;
[0030] S5.2, annealing treatment, placing the alloy block in an annealing furnace under inert gas protection for annealing treatment;
[0031] S5.3. Performance testing: Conduct hydrogen storage performance testing on the annealed alloy block, including the determination of maximum hydrogen storage capacity, hydrogen release rate, and cycle life indicators to ensure that the alloy performance meets the design requirements.
[0032] Preferably, in step S1, the purity of the selected raw metal powder is ≥99.9%, and the powder has no obvious oxidation, agglomeration or impurities.
[0033] Preferably, in step S3, during the smelting process, the high-frequency electromagnetic induction smelting furnace controls the heating rate to be 5-20°C / min, and the smelting temperature is 1300-1600°C.
[0034] Preferably, in step S5, during the annealing treatment, the annealing temperature is 900-1450° C., and the annealing time is 3-5 hours.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The present invention optimizes the alloy composition so that the hydrogen storage alloy has excellent hydrogen storage performance, high cycle stability and long life, and the preparation process is simple and low cost; by optimizing the element ratio and the preparation process, a balance between low cost and high performance is achieved, providing a high-efficiency hydrogen storage material for the field of hydrogen energy storage. DETAILED DESCRIPTION
[0037] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0038] The present invention provides a high-efficiency hydrogen storage alloy material, comprising the following components in percentage by mass:
[0039] Nickel: 49.9% to 51.1%;
[0040] Cobalt: 10.16% to 10.56%;
[0041] Manganese: 4.34% to 4.74%;
[0042] Aluminum: 1.5% to 1.9%;
[0043] Lanthanum: 20.5%-24.5%;
[0044] Cerium: 8.4% to 10.4%;
[0045] Praseodymium: 0.4% to 0.8%;
[0046] Neodymium: 0.4%~0.8%.
[0047] A method for preparing a high-efficiency hydrogen storage alloy material comprises the following steps:
[0048] Step S1, raw material preparation and pretreatment:
[0049] S1.1. Raw material selection: metal powders that meet quality requirements are selected, including nickel powder, cobalt powder, manganese powder, aluminum powder, lanthanum powder, cerium powder, praseodymium powder and neodymium powder;
[0050] S1.2, screening, using an airflow classifier to screen the raw material powder to remove particles larger and smaller than the set particle size;
[0051] S1.3, impurity removal, remove ferromagnetic impurities and non-metallic impurities in the powder by magnetic separation;
[0052] S1.4, drying treatment, placing the screened powder in a vacuum drying oven at a temperature of 80-120°C for 2-4 hours to remove moisture on the powder surface and adsorbed moisture;
[0053] Step S2: Mixing and pressing:
[0054] S2.1, powder mixing, using a ball mill for powder mixing, the speed is 300 ~ 500rpm, the mixing time is 2 ~ 4h, to ensure that the powder is mixed evenly, and anhydrous ethanol can be added as a dispersant during the mixing process to improve the mixing effect;
[0055] S2.2, pressing and molding, pouring the evenly mixed powder into a mold, using a hydraulic press to press, the pressure range is 100 ~ 300MPa, and the pressure holding time is 1 ~ 5min;
[0056] Step S3, smelting and alloying:
[0057] S3.1, during the smelting process, the pressed alloy block is placed in a high-frequency electromagnetic induction melting furnace for smelting, so that the alloy block reaches a melting point above the melting point in a relatively short time, and during the smelting process, the melt is evenly mixed by the stirring effect of electromagnetic induction, and the stirring speed is 50-100 rpm;
[0058] S3.2, repeated smelting, in order to ensure the uniformity of alloy composition and the compactness of structure, multiple smelting is required. After each smelting, the melt is poured out and put back into the furnace, and the above smelting process is repeated 3 to 4 times;
[0059] Step S4: molding and cooling:
[0060] S4.1, pouring molding, quickly pour the molten alloy liquid into a mold preheated to 100-200℃ to avoid cracks caused by excessive cooling of the alloy;
[0061] S4.2, cooling and solidification, the alloy liquid in the mold gradually solidifies and forms the required alloy block under natural cooling;
[0062] Step S5, post-processing:
[0063] S5.1. Surface treatment: sandblasting, grinding or chemical treatment of the formed alloy block to remove surface defects and oxide layers and improve the hydrogen absorption and desorption properties of the alloy;
[0064] S5.2, annealing treatment, placing the alloy block in an annealing furnace under inert gas protection for annealing treatment;
[0065] S5.3. Performance testing: Conduct hydrogen storage performance testing on the annealed alloy block, including the determination of maximum hydrogen storage capacity, hydrogen release rate, and cycle life indicators to ensure that the alloy performance meets the design requirements.
[0066] In step S1 of this embodiment, the purity of the selected raw metal powder is ≥99.9%, and the powder has no obvious oxidation, agglomeration or impurities.
[0067] In step S3 of this embodiment, during the smelting process, the high-frequency electromagnetic induction melting furnace controls the heating rate to be 5-20°C / min, and the smelting temperature is 1300-1600°C.
[0068] In step S5 of this embodiment, during the annealing treatment, the annealing temperature is 900-1450° C. and the annealing time is 3-5 hours.
[0069] Embodiment 1:
[0070] A high-efficiency hydrogen storage alloy material comprises the following components in mass percentage:
[0071] Nickel: 49.9%;
[0072] Cobalt: 10.56%;
[0073] Manganese: 4.34%;
[0074] Aluminum: 1.5%;
[0075] Lanthanum: 20.5%;
[0076] Cerium: 8.4%;
[0077] Praseodymium: 0.4%;
[0078] Neodymium: 0.4%.
[0079] A method for preparing a high-efficiency hydrogen storage alloy material comprises the following steps:
[0080] Step S1, raw material preparation and pretreatment:
[0081] S1.1. Raw material selection: metal powders that meet quality requirements are selected, including nickel powder, cobalt powder, manganese powder, aluminum powder, lanthanum powder, cerium powder, praseodymium powder and neodymium powder;
[0082] S1.2, screening, using an airflow classifier to screen the raw material powder to remove particles larger and smaller than the set particle size;
[0083] S1.3, impurity removal, remove ferromagnetic impurities and non-metallic impurities in the powder by magnetic separation;
[0084] S1.4, drying treatment, placing the screened powder in a vacuum drying oven at 80°C for 2 hours to remove moisture on the powder surface and adsorbed moisture;
[0085] Step S2: Mixing and pressing:
[0086] S2.1, powder mixing, using a ball mill for powder mixing, the speed is 300rpm, the mixing time is 2h, to ensure that the powders are mixed evenly, and anhydrous ethanol can be added as a dispersant during the mixing process to improve the mixing effect;
[0087] S2.2, pressing and molding, pouring the evenly mixed powder into a mold, using a hydraulic press to press, the pressure range is 100MPa, and the holding time is 1min;
[0088] Step S3, smelting and alloying:
[0089] S3.1, during the smelting process, the pressed alloy block is placed in a high-frequency electromagnetic induction melting furnace for smelting, so that the alloy block reaches a melting point above the melting point in a relatively short time, and during the smelting process, the melt is evenly mixed by the stirring effect of electromagnetic induction, and the stirring speed is 50 rpm;
[0090] S3.2, repeated smelting, in order to ensure the uniformity of alloy composition and the compactness of structure, multiple smelting is required. After each smelting, the melt is poured out and put back into the furnace, and the above smelting process is repeated for 3 times;
[0091] Step S4: molding and cooling:
[0092] S4.1. Pouring and molding: quickly pour the molten alloy liquid into a mold preheated to 100°C to avoid cracks caused by excessive cooling of the alloy;
[0093] S4.2, cooling and solidification, the alloy liquid in the mold gradually solidifies and forms the required alloy block under natural cooling;
[0094] Step S5, post-processing:
[0095] S5.1. Surface treatment: sandblasting, grinding or chemical treatment of the formed alloy block to remove surface defects and oxide layers and improve the hydrogen absorption and desorption properties of the alloy;
[0096] S5.2, annealing treatment, placing the alloy block in an annealing furnace under inert gas protection for annealing treatment;
[0097] S5.3. Performance testing: Conduct hydrogen storage performance testing on the annealed alloy block, including the determination of maximum hydrogen storage capacity, hydrogen release rate, and cycle life indicators to ensure that the alloy performance meets the design requirements.
[0098] In step S1 of this embodiment, the purity of the selected raw metal powder is ≥99.9%, and the powder has no obvious oxidation, agglomeration or impurities.
[0099] In step S3 of this embodiment, during the smelting process, the high-frequency electromagnetic induction melting furnace controls the heating rate to be 5°C / min and the smelting temperature to be 1300°C.
[0100] In step S5 of this embodiment, during the annealing treatment, the annealing temperature is 900° C. and the annealing time is 3 hours.
[0101] Embodiment 2:
[0102] A high-efficiency hydrogen storage alloy material comprises the following components in mass percentage:
[0103] Nickel: 51.1%;
[0104] Cobalt: 10.16%;
[0105] Manganese: 4.34%;
[0106] Aluminum: 1.5%;
[0107] Lanthanum: 20.5%;
[0108] Cerium: 8.4%;
[0109] Praseodymium: 0.4%;
[0110] Neodymium: 0.4%.
[0111] A method for preparing a high-efficiency hydrogen storage alloy material comprises the following steps:
[0112] Step S1, raw material preparation and pretreatment:
[0113] S1.1. Raw material selection: metal powders that meet quality requirements are selected, including nickel powder, cobalt powder, manganese powder, aluminum powder, lanthanum powder, cerium powder, praseodymium powder and neodymium powder;
[0114] S1.2, screening, using an airflow classifier to screen the raw material powder to remove particles larger and smaller than the set particle size;
[0115] S1.3, impurity removal, remove ferromagnetic impurities and non-metallic impurities in the powder by magnetic separation;
[0116] S1.4, drying treatment, placing the screened powder in a vacuum drying oven at a temperature of 120°C for 4 hours to remove moisture on the powder surface and adsorbed moisture;
[0117] Step S2: Mixing and pressing:
[0118] S2.1, powder mixing, using a ball mill for powder mixing, the speed is 500rpm, the mixing time is 2 to 4h, to ensure that the powders are mixed evenly, and anhydrous ethanol can be added as a dispersant during the mixing process to improve the mixing effect;
[0119] S2.2, pressing and molding, pouring the evenly mixed powder into a mold, using a hydraulic press to press, the pressure range is 300MPa, and the holding time is 5min;
[0120] Step S3, smelting and alloying:
[0121] S3.1, smelting process, the pressed alloy block is placed in a high-frequency electromagnetic induction melting furnace for smelting, so that the alloy block reaches above the melting point in a relatively short time, and during the smelting process, the melt is evenly mixed by the stirring effect of electromagnetic induction, and the stirring speed is 100rpm;
[0122] S3.2, repeated smelting, in order to ensure the uniformity of alloy composition and the compactness of structure, multiple smelting is required. After each smelting, the melt is poured out and put back into the furnace, and the above smelting process is repeated for 4 times;
[0123] Step S4: molding and cooling:
[0124] S4.1. Pouring and molding: quickly pour the molten alloy liquid into a mold preheated to 200°C to avoid cracks caused by excessive cooling of the alloy;
[0125] S4.2, cooling and solidification, the alloy liquid in the mold gradually solidifies and forms the required alloy block under natural cooling;
[0126] Step S5, post-processing:
[0127] S5.1. Surface treatment: sandblasting, grinding or chemical treatment of the formed alloy block to remove surface defects and oxide layers and improve the hydrogen absorption and desorption properties of the alloy;
[0128] S5.2, annealing treatment, placing the alloy block in an annealing furnace under inert gas protection for annealing treatment;
[0129] S5.3. Performance testing: Conduct hydrogen storage performance testing on the annealed alloy block, including the determination of maximum hydrogen storage capacity, hydrogen release rate, and cycle life indicators to ensure that the alloy performance meets the design requirements.
[0130] In step S1 of this embodiment, the purity of the selected raw metal powder is ≥99.9%, and the powder has no obvious oxidation, agglomeration or impurities.
[0131] In step S3 of this embodiment, during the smelting process, the high-frequency electromagnetic induction melting furnace controls the heating rate to be 20°C / min and the smelting temperature to be 1600°C.
[0132] In step S5 of this embodiment, during the annealing treatment, the annealing temperature is 1450° C. and the annealing time is 5 hours.
[0133] Embodiment 3:
[0134] A high-efficiency hydrogen storage alloy material comprises the following components in mass percentage:
[0135] Nickel: 50%;
[0136] Cobalt: 10.3%;
[0137] Manganese: 4.54%;
[0138] Aluminum: 1.7%;
[0139] Lanthanum: 22.5%;
[0140] Cerium: 9.4%;
[0141] Praseodymium: 0.6%;
[0142] Neodymium: 0.6%.
[0143] A method for preparing a high-efficiency hydrogen storage alloy material comprises the following steps:
[0144] Step S1, raw material preparation and pretreatment:
[0145] S1.1. Raw material selection: metal powders that meet quality requirements are selected, including nickel powder, cobalt powder, manganese powder, aluminum powder, lanthanum powder, cerium powder, praseodymium powder and neodymium powder;
[0146] S1.2, screening, using an airflow classifier to screen the raw material powder to remove particles larger and smaller than the set particle size;
[0147] S1.3, impurity removal, remove ferromagnetic impurities and non-metallic impurities in the powder by magnetic separation;
[0148] S1.4, drying treatment, placing the screened powder in a vacuum drying oven at a temperature of 100°C for 3 hours to remove moisture on the powder surface and adsorbed moisture;
[0149] Step S2: Mixing and pressing:
[0150] S2.1, powder mixing, using a ball mill for powder mixing, the speed is 400rpm, the mixing time is 3h, to ensure that the powders are mixed evenly, and anhydrous ethanol can be added as a dispersant during the mixing process to improve the mixing effect;
[0151] S2.2, pressing and molding, pouring the evenly mixed powder into a mold, using a hydraulic press to press, the pressure range is 200MPa, and the holding time is 3min;
[0152] Step S3, smelting and alloying:
[0153] S3.1, during the smelting process, the pressed alloy block is placed in a high-frequency electromagnetic induction melting furnace for smelting, so that the alloy block reaches a melting point in a relatively short time, and during the smelting process, the melt is evenly mixed by the stirring effect of electromagnetic induction, and the stirring speed is 75 rpm;
[0154] S3.2, repeated smelting, in order to ensure the uniformity of alloy composition and the compactness of structure, multiple smelting is required. After each smelting, the melt is poured out and put back into the furnace, and the above smelting process is repeated for 4 times;
[0155] Step S4: molding and cooling:
[0156] S4.1. Pouring and molding: quickly pour the molten alloy liquid into a mold preheated to 150°C to avoid cracks caused by excessive cooling of the alloy;
[0157] S4.2, cooling and solidification, the alloy liquid in the mold gradually solidifies and forms the required alloy block under natural cooling;
[0158] Step S5, post-processing:
[0159] S5.1. Surface treatment: sandblasting, grinding or chemical treatment of the formed alloy block to remove surface defects and oxide layers and improve the hydrogen absorption and desorption properties of the alloy;
[0160] S5.2, annealing treatment, placing the alloy block in an annealing furnace under inert gas protection for annealing treatment;
[0161] S5.3. Performance testing: Conduct hydrogen storage performance testing on the annealed alloy block, including the determination of maximum hydrogen storage capacity, hydrogen release rate, and cycle life indicators to ensure that the alloy performance meets the design requirements.
[0162] In step S1 of this embodiment, the purity of the selected raw metal powder is ≥99.9%, and the powder has no obvious oxidation, agglomeration or impurities.
[0163] In step S3 of this embodiment, during the smelting process, the high-frequency electromagnetic induction melting furnace controls the heating rate to be 17°C / min, and the smelting temperature is 1450°C.
[0164] In step S5 of this embodiment, during the annealing treatment, the annealing temperature is 1175° C. and the annealing time is 4 hours.
[0165] Embodiment 4:
[0166] A high-efficiency hydrogen storage alloy material comprises the following components in mass percentage:
[0167] Nickel: 50%;
[0168] Cobalt: 10.3%;
[0169] Manganese: 4.54%;
[0170] Aluminum: 1.7%;
[0171] Lanthanum: 22.5%;
[0172] Cerium: 9.4%;
[0173] Praseodymium: 0.6%;
[0174] Neodymium: 0.6%.
[0175] A method for preparing a high-efficiency hydrogen storage alloy material comprises the following steps:
[0176] Step S1, raw material preparation and pretreatment:
[0177] S1.1. Raw material selection: metal powders that meet quality requirements are selected, including nickel powder, cobalt powder, manganese powder, aluminum powder, lanthanum powder, cerium powder, praseodymium powder and neodymium powder;
[0178] S1.2, screening, using an airflow classifier to screen the raw material powder to remove particles larger and smaller than the set particle size;
[0179] S1.3, impurity removal, remove ferromagnetic impurities and non-metallic impurities in the powder by magnetic separation;
[0180] S1.4, drying treatment, placing the screened powder in a vacuum drying oven at 90°C for 2.5 hours to remove moisture on the powder surface and adsorbed moisture;
[0181] Step S2: Mixing and pressing:
[0182] S2.1, powder mixing, using a ball mill for powder mixing, the speed is 350rpm, the mixing time is 2.5h, to ensure that the powders are mixed evenly, and anhydrous ethanol can be added as a dispersant during the mixing process to improve the mixing effect;
[0183] S2.2, pressing and molding, pouring the evenly mixed powder into the mold, using a hydraulic press to press, the pressure range is 150MPa, and the pressure holding time is 2min;
[0184] Step S3, smelting and alloying:
[0185] S3.1, during the smelting process, the pressed alloy block is placed in a high-frequency electromagnetic induction melting furnace for smelting, so that the alloy block reaches a melting point above the melting point in a relatively short time, and during the smelting process, the melt is evenly mixed by the stirring effect of electromagnetic induction, and the stirring speed is 65 rpm;
[0186] S3.2, repeated smelting, in order to ensure the uniformity of alloy composition and the compactness of structure, multiple smelting is required. After each smelting, the melt is poured out and put back into the furnace, and the above smelting process is repeated for 3 times;
[0187] Step S4: molding and cooling:
[0188] S4.1. Pouring and molding: quickly pour the molten alloy liquid into a mold preheated to 150°C to avoid cracks caused by excessive cooling of the alloy;
[0189] S4.2, cooling and solidification, the alloy liquid in the mold gradually solidifies and forms the required alloy block under natural cooling;
[0190] Step S5, post-processing:
[0191] S5.1. Surface treatment: sandblasting, grinding or chemical treatment of the formed alloy block to remove surface defects and oxide layers and improve the hydrogen absorption and desorption properties of the alloy;
[0192] S5.2, annealing treatment, placing the alloy block in an annealing furnace under inert gas protection for annealing treatment;
[0193] S5.3. Performance testing: Conduct hydrogen storage performance testing on the annealed alloy block, including the determination of maximum hydrogen storage capacity, hydrogen release rate, and cycle life indicators to ensure that the alloy performance meets the design requirements.
[0194] In step S1 of this embodiment, the purity of the selected raw metal powder is ≥99.9%, and the powder has no obvious oxidation, agglomeration or impurities.
[0195] In step S3 of this embodiment, during the smelting process, the high-frequency electromagnetic induction melting furnace controls the heating rate to be 15°C / min, and the smelting temperature is 1400°C.
[0196] In step S5 of this embodiment, during the annealing treatment, the annealing temperature is 1100° C. and the annealing time is 3.5 hours.
[0197] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0198] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-efficiency hydrogen storage alloy material, characterized in that: The following ingredients are included in mass percentage: Nickel: 49.9% to 51.1%; Cobalt: 10.16% to 10.56%; Manganese: 4.34% to 4.74%; Aluminum: 1.5% to 1.9%; Lanthanum: 20.5%-24.5%; Cerium: 8.4% to 10.4%; Praseodymium: 0.4% to 0.8%; Neodymium: 0.4%~0.8%.
2. A method for preparing an efficient hydrogen storage alloy material, characterized in that: The following steps are involved: Step S1, raw material preparation and pretreatment: S1.
1. Raw material selection: metal powders that meet quality requirements are selected, including nickel powder, cobalt powder, manganese powder, aluminum powder, lanthanum powder, cerium powder, praseodymium powder and neodymium powder; S1.2, screening, using an airflow classifier to screen the raw material powder to remove particles larger and smaller than the set particle size; S1.3, impurity removal, remove ferromagnetic impurities and non-metallic impurities in the powder by magnetic separation; S1.4, drying treatment, placing the screened powder in a vacuum drying oven at a temperature of 80-120°C for 2-4 hours to remove moisture on the powder surface and adsorbed moisture; Step S2: Mixing and pressing: S2.1, powder mixing, using a ball mill for powder mixing, the speed is 300 ~ 500rpm, the mixing time is 2 ~ 4h, to ensure that the powder is mixed evenly, and anhydrous ethanol can be added as a dispersant during the mixing process to improve the mixing effect; S2.2, pressing and molding, pouring the evenly mixed powder into a mold, using a hydraulic press to press, the pressure range is 100 ~ 300MPa, and the pressure holding time is 1 ~ 5min; Step S3, smelting and alloying: S3.1, during the smelting process, the pressed alloy block is placed in a high-frequency electromagnetic induction melting furnace for smelting, so that the alloy block reaches a melting point above the melting point in a relatively short time, and during the smelting process, the melt is evenly mixed by the stirring effect of electromagnetic induction, and the stirring speed is 50-100 rpm; S3.2, repeated smelting, in order to ensure the uniformity of alloy composition and the compactness of structure, multiple smelting is required. After each smelting, the melt is poured out and put back into the furnace, and the above smelting process is repeated 3 to 4 times; Step S4: molding and cooling: S4.1, pouring molding, quickly pour the molten alloy liquid into a mold preheated to 100-200℃ to avoid cracks caused by excessive cooling of the alloy; S4.2, cooling and solidification, the alloy liquid in the mold gradually solidifies and forms the required alloy block under natural cooling; Step S5, post-processing: S5.
1. Surface treatment: sandblasting, grinding or chemical treatment of the formed alloy block to remove surface defects and oxide layers and improve the hydrogen absorption and desorption properties of the alloy; S5.2, annealing treatment, placing the alloy block in an annealing furnace under inert gas protection for annealing treatment; S5.
3. Performance testing: Conduct hydrogen storage performance testing on the annealed alloy block, including the determination of maximum hydrogen storage capacity, hydrogen release rate, and cycle life indicators to ensure that the alloy performance meets the design requirements.
3. The method for preparing a high-efficiency hydrogen storage alloy material according to claim 2, characterized in that: In step S1, the purity of the selected raw metal powder is ≥99.9%, and the powder has no obvious oxidation, agglomeration or impurities.
4. The method for preparing a high-efficiency hydrogen storage alloy material according to claim 2, characterized in that: In step S3, during the smelting process, the high-frequency electromagnetic induction smelting furnace controls the heating rate to be 5-20°C / min, and the smelting temperature to be 1300-1600°C.
5. The method for preparing a high-efficiency hydrogen storage alloy material according to claim 2, characterized in that: In step S5, during the annealing treatment, the annealing temperature is 900-1450° C. and the annealing time is 3-5 hours.
Citation Information
Patent Citations
Hydrogen storage alloy material for nickel-hydrogen battery and preparation method thereof
CN102634692A
AB5-BASED HYDROGEN STORAGE ALLOY, ELECTRODE FOR Ni-MH BATTERY, SECONDARY BATTERY, AND PREPARATION METHOD OF HYDROGEN STORAGE ALLOY
US20220006070A1
Cited By
Manganese-copper alloy material with stable resistance and preparation method thereof
CN119464832A
